Determinants Of Non-Performing Loans In Indonesia - Yohana Wahyu Prasetyowatie; Sugeng Hariadi (Trunojoyo University of Madura, 2022)
Non-performing loans (NPLs) are a typical sign of stress testing from financial institutions and may be used to measure the financial system's health. The critical criterion for achieving financial system stability is macroeconomic stability. Instability in the financial system (financial crisis) impairs a bank's liquidity and might lead to more problematic loans, impacting other industries. The association between NPL and numerous macroeconomic variables, including Interest Rate Spreads, Inflation, Percentage of Open Disruption, and Amount of Foreign Exchange Reserves in Indonesia, is examined in this paper. The study used the Vector Error Correction Model (VECM) method to estimate data for a sample period of 2000 to 2020. In the long run, inflation factors, the number of open jobless, and the number of foreign exchange reserves all substantially impacted the ratio of non-performing loans, according to the findings. However, no variables influenced the percentage of non-performing loans in the short run.